“A STUDY TO ASSESS THE EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ON KNOWLEDGE REGARDING FIRST AID FOR BURNS AND ITS PREVENTION AMONG MOTHERS OF UNDER FIVE CHILDREN IN SELECTED RURAL AREA OF KANPUR U.P.” (International Journal of Food and Nutritional Sciences, 2021)
A retrospective study was conducted to study the incidence, severity, extent, cause, risk factorsand overall mortality. 309 children of burn injuries treated over last 10 years in Govt. Hospital, KanpurIndia. The study found that the children of less than 5 years were affected 76.1% and more than childrenage >5 years is 23.9%. Females were affected 74.1% and males are affected 25.9%. Most of the childrenreceived burn injuries in the range of 0-20percent. Body surface area 63.1 percent, electric burn 3.% scald72.5 % followed by flame 22.7 % were most common cause of burn injuries. Overall pediatric burnmortality was 7.4 percent.